New aromatic lactone derivatives with inhibitory activities on nitric oxide production from Homalium stenophyllum. (June 2018) - Wu, Shou-Yuan; Fu, Yan-Hui; Zhou, Qi; Bai, Meng; Chen, Guang-Ying; Zhao, Si-Yu; Song, Xiao-Ping; Han, Chang-Ri
Graphical abstract: Highlights: The constituents of the stems of Homalium stenophyllum were investigated. Two new aromatic lactone derivatives were isolated from H . stenophyllum . The inhibitory activities on NO production of 1 and 2 were evaluated in vitro . Compounds 1 and 2 exhibited inhibitory effects with IC50 values of 12.25 ± 0.45 and 25.36 ± 1.65 μM. Abstract: Two new aromatic lactone derivatives, homastenones A (1 ) and B (2 ), together with six known compounds (3 –8 ), were isolated from the stems of Homalium stenophyllum . Their structures were established on the basis of extensive spectroscopic analyses. Among them, homastenones A (1 ) and B (2 ) are two novel aromatic lactone derivatives containing 12 carbon atoms on the carbon skeleton, and the known compounds (3 –8 ) were isolated from this plant for the first time. All new compounds were evaluated for their inhibitory activities on nitric oxide (NO) production induced by lipopolysaccharide in mouse macrophage RAW 264.7 cells in vitro . Compounds1 and2 exhibited inhibitory activities with IC50 values of 12.25 ± 0.45 and 25.36 ± 1.65 μM, respectively.